2021
DOI: 10.1007/s00421-021-04798-y
|View full text |Cite
|
Sign up to set email alerts
|

Physiological effects of mixed-gas deep sea dives using a closed-circuit rebreather: a field pilot study

Abstract: Purpose Deep diving using mixed gas with closed-circuit rebreathers (CCRs) is increasingly common. However, data regarding the effects of these dives are still scarce. This preliminary field study aimed at evaluating the acute effects of deep (90-120 msw) mixed-gas CCR bounce dives on lung function in relation with other physiological parameters. Methods Seven divers performed a total of sixteen open-sea CCR dives breathing gas mixture of helium, nitrogen and oxygen (trimix) within four days at 2 depths (90 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 37 publications
2
13
1
Order By: Relevance
“…In particular, brain imaging studies showed that HRV is correlated with brain networks that are responsible for the judgment of stressful situations (e.g., the ventromedial prefrontal cortex). This perspective supports the utilization of HRV for the objective investigation of stress-induced events [ 12 ]. In confirmation of this view, increased occupational stress was associated with reduced HRV [ 15 ].…”
Section: Introductionsupporting
confidence: 74%
See 4 more Smart Citations
“…In particular, brain imaging studies showed that HRV is correlated with brain networks that are responsible for the judgment of stressful situations (e.g., the ventromedial prefrontal cortex). This perspective supports the utilization of HRV for the objective investigation of stress-induced events [ 12 ]. In confirmation of this view, increased occupational stress was associated with reduced HRV [ 15 ].…”
Section: Introductionsupporting
confidence: 74%
“…The observed positive association between the mean HRV and AEA at baseline could be better understood by considering the biological meaning of both HRV and AEA. Indeed, high HRV is linked with controlling and homeostatic autonomic nervous system operations, which increase the body’s aptitude to manage the distress conditions [ 12 ], whereas stress-induced events reduce AEA levels [ 6 ]. Though there is evidence indicating a negative association between AEA and stress, the principal processes eliciting this phenomenon are debatable.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations